TEACHER PERCEPTION OF CITIZENSHIP IN SCIENCE LEARNING TOOLS IN UNIFORM STRAIGHT MOTION AND UNIFORMLY ACCELERATED STRAIGHT MOTION - Insani Putri, Fhadira; Purwaningsih, Sri; Asrial, Asrial (EduFisika: Jurnal Pendidikan Fisika, 2025)
This research aims to analyze teacher perceptions of Citizenship in Science learning tools designed to develop critical thinking skills in physics, specifically for Regular Straight Motion and Regular Changing Straight Motion materials. Using a mixed-method approach with an explanatory sequential design, data was collected from 9 junior high school science teachers through both quantitative questionnaires and qualitative interviews. The research employed purposive sampling to ensure participants had direct experience teaching the relevant physics concepts. Quantitative data was analyzed descriptively while qualitative data was processed using the Miles and Huberman method. Results indicate that teachers perceive the learning tools very positively with an average rating of 90.06%, particularly appreciating the systematic design, content clarity, critical thinking facilitation, and 21st century learning integration. The novelty of this study lies in its explicit integration of Citizenship in Science approaches with critical thinking development in physics education, providing a framework that connects theoretical physics concepts with real-world applications and civic responsibility. This research contributes to understanding the potential implementation challenges and opportunities for innovative physics learning tools in classroom settings. The findings imply that physics education can be enhanced through tools that not only develop conceptual understanding but also foster critical thinking skills necessary for scientific citizenship, though further classroom implementation studies with larger samples are needed to validate effectiveness.